THE CRUSADES AND THEIR INFLUENCE ON EUROPE - Asror Pardayev; Hasanova Marjona (Journals Park Publishing, 2022)
Human history, unfortunately, is not always a world of discoveries and achievements, but often includes a chain of countless wars. One such war is the Crusades, which took place in the XI-XIII centuries. This article discusses the final Seventh and Eighth Crusades and their impact, consequences, and results on Europe.
Keywords: Louis IX,; Bibars,; Charles of Anjou